High-entropy phosphide electrocatalyst as well as preparation method and application thereof

The FeCoNiCuMnP high-entropy phosphide electrocatalyst is supported on a titanium substrate or carbon cloth, and the poor performance of alcohol oxidation electrocatalyst is solved, and the efficient and low-cost methanol oxidation reaction is achieved, which improves the efficiency and environmental protection of hydrogen production.

CN119307954APending Publication Date: 2025-01-14FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310870205.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The performance of alcohol oxidation electrocatalysts is poor, which hinders the efficiency and stability of methanol oxidation reaction and affects the efficiency and environmental protection of hydrogen production.

Method used

FeCoNiCuMnP high-entropy phosphide electrocatalyst is used to form high-entropy phosphide nanoparticles by loading on a titanium substrate or carbon cloth, and by solvothermal reaction and phosphorylation treatment, thereby improving the conductivity and catalytic activity of the catalyst.

Benefits of technology

It significantly improves the performance of methanol oxidation reaction, achieves efficient and low-cost hydrogen production, the voltage of the electrocatalytic anode in 1.0mol/L methanol is 1.31V vs. RHE, the formate Faraday efficiency exceeds 90%, and the catalyst has good wear resistance and resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307954A_ABST
    Figure CN119307954A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy phosphide electrocatalyst as well as a preparation method and application thereof, and belongs to the technical field of electrochemical materials. The preparation method comprises the following steps: S1, obtaining solutions of cobalt salt, nickel salt, copper salt and manganese salt, and mixing to form a blended solution A; s2, obtaining a complexing agent solution B; the complexing agent is selected from K4Fe (CN) 6 and / or K3Fe (CN) 6; s3, mixing the blended solution A and the solution B, and carrying out a coprecipitation reaction to obtain a transition metal HEPBA precursor precipitation mixture C; s4, mixing the transition metal HEPBA precursor precipitate mixture C, a solvent and a substrate, and performing solvothermal reaction to obtain a product I; and S5, roasting the product I and a phosphoric acid compound in an inert atmosphere, and cooling to obtain a product II which is the FeCoNiCuMnP high-entropy phosphide electrocatalyst. The electrocatalyst can be used for preparing formate through electrocatalytic oxidation of methanol and has a good catalytic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical materials, and in particular relates to a high entropy phosphide electrocatalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen has large reserves on the earth, high gravitational energy density, is clean, has no carbon emissions, and is renewable. It is generally considered to be one of the most promising ideal energy carriers for decarbonization and plays an important role in solving the global energy and environmental crisis. So far, hydrogen is mainly obtained through the reforming process of fossil fuels, and this production method has caused great trouble to people due to its complex operation and the presence of carbon dioxide emissions. Scientists have studied the use of electrochemical methods to produce hydrogen through overall water splitting (OWS), that is, through the hydrogen evolution reaction (HER), which is one of the most promising methods. However, compared with HER, OER requires four electron transfers, and the inherent thermodynamic energy barrier of anodic oxidation leads to slow overall reaction kinetics. Therefore, it is necessary to overcome a higher overpotential and require a fairly high theoretical potential (1.23V), which seriously hinders its efficiency. This is the main reason that hinders the development of water electrolysis systems. In addition, the value of the product oxygen produced at the anode is low, and the mixture of H2 / O2 is prone to explosion. Scientific research proposes to replace the slow OER by using more thermodynamically favorable oxidation reactions, especially those that can produce value-added products. Therefore, it is crucial to select a widely used, highly active, simple, low-priced, and easily oxidizable small molecule, such as alcohol, hydrazine, urea, etc., for our research. Perform electrochemical oxidation reactions to replace OER and achieve energy-saving H2 production. Methanol is the simplest alcohol. Due to its simplest structure, it is an ideal substrate molecule for anodic oxidation, with low cost and extensive resources, and can replace OER. Methanol has a low oxidation potential (0.58V), so pairing the cathode hydrogen evolution reaction with the kinetically faster methanol oxidation reaction (MOR) can easily achieve efficient, energy-saving, and environmentally friendly H2 production. At the same time, formate, as one of the products of the partial methanol oxidation reaction (MOR), is a key chemical intermediate with a price of about 4 times that of methanol, and it is of great significance to highly selectively convert methanol into value-added formate instead of carbon dioxide. In the above alcohol oxidation process, the catalytic activity and stability of the electrochemical catalyst are crucial to the entire reaction process. Summary of the invention

[0003] In view of this, the present invention provides a high entropy phosphide electrocatalyst and a preparation method and application thereof, the main purpose of which is to solve the technical problem of poor performance of alcohol oxidation electrocatalysts.

[0004] On the one hand, the present invention provides a high entropy phosphide electrocatalyst, which includes an active ingredient and a conductive substrate; the active ingredient includes FeCoNiCuMnP high entropy phosphide nanoparticles; the FeCoNiCuMnP high entropy phosphide nanoparticles are loaded on the surface of the conductive substrate.

[0005] Optionally, the conductive substrate includes at least one of a titanium substrate, a nickel substrate, and a carbon cloth.

[0006] The electrocatalyst of the present invention is FeCoNiCuMnP high entropy phosphide nanoparticles loaded on a substrate and evenly distributed; the titanium substrate or nickel substrate or carbon cloth can improve the conductivity of the electrocatalyst and greatly improve the performance of catalytic oxidation of methanol.

[0007] The high entropy phosphide selected in the present invention has the advantages of adjustable composition, complex surface, high tolerance, etc. The high entropy phosphide contains five main elements of FeCoNiCuMn and unique properties (good hardness, high strength, and enhanced wear resistance). It can form more new active sites in multiple adjacent elements, and the interaction can be regulated by reasonably selecting element configuration and composition to improve the catalytic performance.

[0008] In a second aspect, the present invention provides a method for preparing a high entropy phosphide electrocatalyst, the preparation method comprising the following steps:

[0009] S1: obtaining solutions of cobalt salt, nickel salt, copper salt and manganese salt, and mixing them to form a blended solution A;

[0010] S2: Obtaining a complexing agent solution B; the complexing agent is selected from K4Fe(CN)6 and / or K3Fe(CN)6;

[0011] S3: the blended solution A in step S1 and the solution B in step S2 are mixed, and a transition metal HEPBA precursor precipitation mixture C is obtained after a coprecipitation reaction;

[0012] S4: the transition metal HEPBA precursor precipitation mixture C in step S3, the solvent and the substrate are mixed, and a product I is obtained after a solvothermal reaction;

[0013] S5: The product I in step S4 and the phosphoric acid compound are calcined in an inert atmosphere, and then cooled to obtain a product II, wherein the product II is a FeCoNiCuMnP high entropy phosphide electrocatalyst.

[0014] In the above-mentioned product I in step S4 of the present invention, a part of the transition metal HEPBA precursor precipitation mixture C is successfully loaded on the surface of the substrate, and another part of the transition metal HEPBA precursor precipitation mixture C is not loaded on the surface of the substrate but exists alone; both products can be used as electrocatalysts for methanol oxidation reaction; the above-mentioned solid product is dried to form a dry transition metal HEPBA precursor precipitation mixture C loaded on the substrate; the liquid product is centrifuged and dried to obtain a dry powder of the transition metal HEPBA precursor precipitation mixture C.

[0015] The calcination of the product I and the phosphoric acid compound in step S5 of the present invention specifically refers to the solid product attached to the substrate after drying being phosphated and the dry powder after separation and drying of the above-mentioned liquid product being phosphated to form two high entropy phosphides (HEP) with different forms and morphologies, namely, a high entropy phosphide loaded on the substrate and a high entropy phosphide not loaded on the substrate. Both phosphides have electrocatalytic performance in methanol oxidation reaction, and the high entropy phosphide loaded on the substrate has better performance as an electrocatalyst.

[0016] In the metal salt raw material of the present invention, cobalt salt can be replaced by iron salt; in the complexing agent of the present invention, K4Fe(CN)6 or K3Fe(CN)6 can be replaced by K3Co(CN)6; but iron salt and K4Fe(CN)6 or K3Fe(CN)6 cannot exist in the raw material or the complexing agent at the same time, and cobalt salt (nitrate or halide) and K3Co(CN)6 cannot exist in the raw material or the complexing agent at the same time.

[0017] The invention adopts a coprecipitation method to prepare a FeCoNiCuMn high entropy compound, the process is controllable, the operation is simple, and a nano powder material with a small particle size and uniform distribution can be easily prepared.

[0018] The present invention phosphates the FeCoNiCuMn-PBA high entropy Prussian blue analogue into the FeCoNiCuMnP high entropy phosphide electrocatalyst because the high entropy Prussian blue analogue has poor electrical conductivity, and the phosphating treatment increases the electrical conductivity of the material, improves the catalytic performance of the material, and is more suitable as an electrocatalyst for the methanol oxidation reaction.

[0019] Optionally, the cobalt salt, the nickel salt, the copper salt or the manganese salt in step S1 are all selected from chlorides and / or nitrates; they may also be selected from other applicable salts according to actual needs.

[0020] Optionally, the molar ratio of the cobalt salt, the nickel salt, the copper salt and the manganese salt in step S1 is 1:1:1:1. The content of each component of high entropy Prussian blue can also be adjusted within a limited range according to actual needs.

[0021] Optionally, the substrate in step S4 is selected from at least one of porous titanium foam, titanium mesh, titanium sheet, porous nickel foam, and carbon cloth.

[0022] Optionally, the pretreatment process of the porous titanium foam, titanium mesh, titanium sheet, porous nickel foam and other substrates needs to be ultrasonically treated with acetone and anhydrous ethanol for 5 minutes, ultrasonically treated with dilute hydrochloric acid with a mass fraction of 1 mol / L for 15 minutes, and finally washed with deionized water for 5 minutes and dried; the carbon cloth needs to be treated in a 70°C oil bath in 0.5M H2SO4 for 1 hour, and in a 80°C oil bath in 30% H2O2 for 1 hour, and finally washed with deionized water and dried.

[0023] Optionally, in step S3, the molar ratio of the total amount of the cobalt salt, the nickel salt, the copper salt and the manganese salt to the complexing agent is 6.5-9 mmol: 3-3.5 mmol.

[0024] Optionally, the molar ratio of the total amount of the cobalt salt, the nickel salt, the copper salt and the manganese salt to the complexing agent is selected from 6.5:3, 7:3.1, 7.5:3.2, 8:3.3, 8.5:3.4 or 9:3.5.

[0025] Optionally, step S3-4 is also included between step S3 and step S4: the transition metal HEPBA precursor precipitation mixture C in step S3 is first subjected to aging, separation, water washing, alcohol washing, and drying treatment to obtain a purified solid transition metal HEPBA precursor precipitation mixture C, which is then mixed with a solvent and a substrate for a solvothermal reaction.

[0026] Optionally, the phosphoric acid compound in step S5 includes sodium hypophosphite. A compound containing phosphorus element can also be selected according to actual needs.

[0027] Optionally, the weight ratio of the sodium hypophosphite to the purified solid transition metal HEPBA precursor precipitation mixture C is 5 to 10:1.

[0028] Optionally, the weight ratio of the sodium hypophosphite to the purified solid transition metal HEPBA precursor precipitation mixture C is selected from any value of 5, 6, 7, 8, 9, 10 or a range between any two of them.

[0029] The ratio of the usage amount of the substrate and the total amount of the transition metal salt in the present invention can be adjusted according to actual needs.

[0030] The purpose of selecting a substrate in the present invention is, on the one hand, to prevent the high entropy alloy particles from agglomerating; on the other hand, the conductive substrate is conducive to the efficient mass transfer of the high entropy alloy nanoparticles, good electronic conductivity and good physical contact with the electrode, which can greatly improve the performance of catalytic oxidation of methanol.

[0031] Optionally, the specific preparation process of the blend solution A in step S1 includes: dissolving cobalt salt, nickel salt, copper salt and manganese salt in solvent A, and performing ultrasonic dispersion after dissolution to obtain the blend solution A; the solvent A is selected from deionized water;

[0032] The ratio of the solvent A to the total amount of the cobalt salt, the nickel salt, the copper salt and the manganese salt is 150-200 mL: 6.5-9 mmol.

[0033] Optionally, the molar ratio of the volume of the solvent A to the total amount of the cobalt salt, nickel salt, copper salt and manganese salt is selected from 150ml:6.5mmol, 160ml:7mmol, 170ml:7.5mmol, 180ml:8mmol, 190ml:8.5mmol or 200ml:9mmol.

[0034] Optionally, citric acid and / or citrate are further added to the blended solution A in step S1; the ratio of the citric acid or the citrate to the solvent A is 150-200 mL: 1-1.5 g.

[0035] Optionally, the volume ratio of the solvent A to the mass ratio of (citric acid) citrate is selected from 150 ml: 1 g, 160 ml: 1.1 g, 170 ml: 1.2 g, 180 ml: 1.3 g, 190 ml: 1.4 g or 200 ml: 1.5 g.

[0036] Optionally, the specific preparation process of the complexing agent solution B in step S2 includes: dissolving the complexing agent in solvent B, and performing ultrasonic dispersion after dissolution to obtain the solution B;

[0037] The ratio of the solvent B to the complexing agent is 100-150 mL: 3-3.5 mmol;

[0038] The solvent B is selected from deionized water.

[0039] Optionally, the molar ratio of the volume of the solvent B to the complexing agent is selected from 100 ml: 3 mmol, 110 ml: 3.1 mmol, 120 ml: 3.2 mmol, 130 ml: 3.3 mmol, 140 ml: 3.4 mmol or 150 ml: 3.5 mmol.

[0040] Optionally, the volume ratio of the solvent A to the solvent B is 150-200 mL:100-150 mL.

[0041] Optionally, the volume ratio of solvent A to solvent B is selected from 150:100, 160:110, 170:120, 180:130, 190:140 or 200:150.

[0042] Optionally, the solvent used in the solvothermal reaction in step S4 includes deionized water;

[0043] The reaction temperature of the solvent thermal reaction is 100-160° C., and the reaction time is 6-24 hours.

[0044] Optionally, the reaction temperature of the solvothermal reaction is selected from any value of 100°C, 120°C, 130°C, 140°C, 150°C, 160°C, or a range between any two values;

[0045] The reaction time is selected from any value among 6h, 12h, 18h, 24h or a range value between any two values.

[0046] Optionally, the calcination temperature in step S5 is 1°C / min to 2°C / min, the calcination temperature is 350 to 400°C, and the holding time is 2 to 3h.

[0047] Optionally, the calcination temperature is selected from any value of 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or any range between the two;

[0048] The calcination time is selected from any value among 2, 2.5, 3 hours or any range between the two.

[0049] In a third aspect, the present invention provides an electrocatalytic anode, wherein the material of the electrocatalytic anode includes the above-mentioned high entropy phosphide electrocatalyst or the high entropy phosphide electrocatalyst prepared by the above-mentioned method.

[0050] In a fourth aspect, the present invention provides the use of the above-mentioned electrocatalytic anode in the electrocatalytic oxidation of methanol to produce formate.

[0051] Optionally, the electrocatalytic anode reaches 10 mA cm in an alkaline system of 1.0 mol / L methanol during the electrocatalytic methanol oxidation reaction. -2 The voltage required for the current density is 1.31~1.45V vs.RHE, and the Tafel slope is 79~130mV dec -1 .

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] 1) The high entropy phosphide provided by the present invention has the advantages of adjustable composition, complex surface, high tolerance, etc. The high entropy phosphide contains five main elements of FeCoNiCuMn and unique properties (good hardness, high strength, and enhanced wear resistance). It can form more new active sites in multiple adjacent elements, and the interaction can be regulated by reasonably selecting element configuration and composition, thereby improving the catalytic performance.

[0054] 2) The present invention adopts solvent thermal growth and phosphating treatment with a phosphorus source in an inert atmosphere by a tubular furnace.

[0055] 3) The FeCoNiCuMnP high entropy phosphide nanoparticle catalyst of the present invention can be used for the electrocatalytic oxidation of methanol to formate. The electrocatalytic anode can reach 10 mA cm in 1.0 mol / L KOH containing 1.0 mol / L methanol. -2 The voltage required for the current density was 1.31 V vs. RHE. At a constant voltage of 1.525 V for 50 h, the Faradaic efficiency of formate exceeded 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The X-ray powder diffraction (XRD) pattern of the catalyst material FeCoNiCuMnP-NPs not loaded with nickel prepared in Example 1 of the present invention;

[0057] Figure 2 This is a scanning electron microscope (SEM) image of the catalyst material FeCoNiCuMnP-NPs not loaded with nickel prepared in Example 1 of the present invention;

[0058] Figure 3 This is a transmission electron microscope (TEM) image of the catalyst material FeCoNiCuMnP-NPs not supported on nickel prepared in Example 1 of the present invention;

[0059] Figure 4 This is a transmission electron microscopy scanning element distribution diagram of the catalyst material FeCoNiCuMnP-NPs not loaded with nickel prepared in Example 1 of the present invention;

[0060] Figure 5 This is a scanning electron microscope (SEM) image of the catalyst material FeCoNiCuMnP / NF loaded on porous nickel foam prepared in Example 1 of the present invention;

[0061] Figure 6 This is a linear sweep voltammetry (LSV) curve of the catalyst material FeCoNiCuMnP / NF loaded on porous nickel foam prepared in Example 1 of the present invention in the oxygen evolution reaction. DETAILED DESCRIPTION

[0062] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0063] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0064] In the embodiment of the present invention, the electrochemical performance test of the samples was conducted using a CHI760E electrochemical workstation produced by Shanghai Chenhua Company.

[0065] The X-ray powder diffraction (XRD) of the samples was carried out on an X-ray powder diffractometer (Miniflex600) using Cu Kα radiation ( 15mA,40kV) test.

[0066] The morphology and structure of the samples were characterized by scanning electron microscopy (SEM, Hitachi SU-8010) and transmission electron microscopy (TEM, TECNAIG2 F20).

[0067] The sample products were analyzed using a nuclear magnetic resonance EC-60OR instrument.

[0068] Example 1 (Foam nickel loaded FeCONiCuMnP nano high entropy phosphide catalyst)

[0069] 1. The porous nickel foam was ultrasonically treated with acetone and anhydrous ethanol for 5 minutes, and with 1 mol / L dilute hydrochloric acid for 15 minutes. Finally, it was washed with deionized water for 5 minutes and dried.

[0070] 2. Take 0.35mmol potassium ferrocyanide trihydrate, add it to 150mL deionized water solution, ultrasonicate for 3min to form solution B; 0.2mmol copper nitrate trihydrate, 0.2mmol nickel nitrate hexahydrate, 0.2mmol cobalt nitrate hexahydrate, 0.2mmol manganese nitrate tetrahydrate, 1g trisodium citrate dihydrate are added to 200mL deionized water in sequence, and stirring is continued for 10min at room temperature to form solution A, and then A is poured into B and stirring is continued for 30min to form precipitate C.

[0071] 3. The precipitate C was aged for 18 h, the supernatant was discarded, and then centrifuged and washed with deionized water and ethanol. Finally, the centrifuged and washed items were placed in a 70°C vacuum dryer for drying to form a HEPBA precursor (high entropy Prussian blue analog precursor).

[0072] 4. Weigh 0.05g of the dried HEPBA precursor and transfer it to a 50mL hydrothermal reactor, add 30ml of deionized water, and perform ultrasonic treatment for 10min. Place the pre-treated 3cm*2cm nickel foam in the reactor. Then place the hydrothermal reactor at 120℃ for 18h, cool the reactor naturally to room temperature, take out the nickel foam (the surface of the nickel foam has been loaded with the HEPBA precursor), and clean it with deionized water and alcohol to obtain the nickel foam loaded with HEPBA; centrifuge the liquid (the liquid contains the remaining HEPBA precursor not loaded on the nickel foam), and place it in a vacuum drying oven at 70℃ to dry overnight to obtain the HEPBA precursor powder not loaded on nickel.

[0073] 5. Weigh 0.5 g of sodium hypophosphite monohydrate and put it into a porcelain boat and place it upstream of the gas flow. Put the HEPBA precursor powder and nickel foam that have been dried after hydrothermal treatment into the porcelain boat. Place it in an argon atmosphere and heat it to 350°C at a heating rate of 2°C per minute and calcine it for 3 hours. Perform phosphating treatment and cool it naturally to room temperature to obtain the target material. Among them, part of the product is the electrocatalyst FeCoNiCuMnP-NPs not loaded on the nickel substrate, and part of the product is the electrocatalyst FeCoNiCuMnP / NF loaded on the nickel foam.

[0074] Example 2 (Carbon cloth supported FeCONiCuMnP nano high entropy phosphide catalyst)

[0075] 1. Cut the commercial carbon cloth into the required size (2cm×2cm), boil it in 0.5M H2SO4 and 30% H202 in an 80℃ oil bath for 1 hour, wash it with deionized water and dry it for later use.

[0076] 2. Take 0.35mmol potassium ferrocyanide trihydrate and add it to 150mL of deionized water solution, ultrasonicate for 3min to form solution B; 0.2mmol copper nitrate trihydrate, 0.2mmol nickel nitrate hexahydrate, 0.2mmol cobalt nitrate hexahydrate, 0.2mmol manganese nitrate tetrahydrate, and 1g trisodium citrate dihydrate are added to 200mL of deionized water in sequence, and stirring is continued for 10min at room temperature to form solution A, and then A is poured into B and stirring is continued for 30min to form precipitate C.

[0077] 3. The precipitate C was aged for 18 h, the supernatant was discarded, and then centrifuged and washed with deionized water and ethanol. Finally, the centrifuged and washed items were placed in a 70°C vacuum dryer for drying to form a HEPBA precursor (high entropy Prussian blue precursor).

[0078] 4. Weigh 0.05g of the dried HEPBA precursor and transfer it to a 50mL hydrothermal reactor, add 30ml of deionized water, and ultrasonicate for 10min. Place the pre-treated 3cm*2cm carbon cloth in the reactor. Then place the hydrothermal reactor at 120℃ for 18h, cool the reactor naturally to room temperature, take out the carbon cloth (the surface of the carbon cloth has been loaded with HEPBA precursor), clean it with deionized water and alcohol, centrifuge the liquid (the liquid contains the remaining HEPBA precursor not loaded on the carbon cloth), and place it in a vacuum drying oven at 70℃ to dry overnight to obtain the HEPBA precursor powder not loaded on the carbon cloth.

[0079] 5. Weigh 0.5 g of sodium hypophosphite monohydrate and put it into a porcelain boat and place it upstream of the gas flow. Put the HEPBA precursor powder and carbon cloth that have been dried after hydrothermal treatment into the porcelain boat. Place it in an argon atmosphere and heat it to 350°C at a heating rate of 2°C per minute and calcine it for 3 hours. Perform phosphating treatment and cool it naturally to room temperature to obtain the target material. Among them, part of the product is the electrocatalyst FeCoNiCuMnP-NPs not loaded on the carbon cloth, and part of the product is the electrocatalyst FeCoNiCuMnP / CC loaded on the carbon cloth.

[0080] Application Example 1 (FeCoNiCuMnP nano high entropy alloy catalyst used in oxygen evolution and methanol oxidation electrocatalytic reaction)

[0081] The nickel foam electrode sheet with the in-situ growth of the FeCoNiCuMnP high entropy phosphide nanoparticle catalyst in Example 1 was subjected to a linear sweep curve (LSV) test on an electrochemical workstation, and the electrolytes were:

[0082] (1) The electrolyte is 1.0 mol / L KOH and 1.0 mol / L methanol, and the catalytic methanol oxidation reaction (MOR) performance is tested.

[0083] (2) The electrolyte is 1.0 mol / L KOH, and the oxygen evolution reaction (OER) performance is tested.

[0084] (3) The linear scanning curves of the electrode in the above two electrolytes are as follows Figure 6 As shown in the figure (curve 1 is methanol oxidation, curve 2 is oxygen evolution reaction), it can be seen that in 1.0 mol / L KOH, the OER reaction occurs on the surface of the anode electrode sheet. After adding 1.0 mol / L methanol solution, the MOR reaction occurs first on the surface of the anode electrode sheet. When the voltage is around 1.29 V vs. RHE, the corresponding oxidation current increases rapidly and reaches 10 mA cm -2 The required potential is 1.31 V vs. RHE.

[0085] The electrocatalyst prepared in Example 1 or Example 2 of the present invention includes two forms, one is an electrocatalyst loaded on a substrate, and the other is an electrocatalyst not loaded on a substrate. Both of these electrocatalysts can be used as electrode materials to catalyze methanol oxidation reactions.

[0086] Comparative Example 1

[0087] The difference between Comparative Example 1 and Application Example 1 is that Mo-Co4N is used as the electrocatalytic anode material to catalyze methanol to formate. The result is that when the current is 10 mA cm -2 The voltage reaches 1.36V vs.RHE.

[0088] Comparative Example 2

[0089] The difference between Comparative Example 2 and Application Example 1 is that (Co(OH)2@HOS / CP) is used as the electrocatalytic anode material to catalyze methanol to formate. The result is that when the current is 10 mA cm -2 The voltage reaches 1.397V vs.RHE.

[0090] Comparative Example 3

[0091] The difference between Comparative Example 3 and Application Example 1 is that the unphosphated HEPBA-loaded nickel foam is used as the electrocatalytic anode material to catalyze methanol to formate. The result is that when the current is 10 mA cm -2 The voltage reaches 1.504V vs.RHE.

[0092] Comparative Example 4

[0093] The difference between Comparative Example 4 and Application Example 1 is that the electrocatalyst FeCoNiCuMnP-NPs which is not loaded on the nickel substrate after phosphating is used as the electrocatalytic anode material to catalyze methanol to formate. The result is that when the current is 10 mA cm -2 The voltage reaches 1.38V vs.RHE.

[0094] It can be proved through the above-mentioned Application Example 1 that the electrocatalytic anode material prepared by using the FeCoNiCuMnP high entropy phosphide electrocatalyst of the present invention has excellent electrochemical properties and can be successfully applied to the methanol oxidation reaction.

[0095] The methanol oxidation potential in Application Example 1 of the present invention is 1.31 V vs. RHE, the methanol oxidation potential in Comparative Example 1 is 1.36 V vs. RHE, the voltage in Comparative Example 2 reaches 1.397 V vs. RHE, the voltage in Comparative Example 3 reaches 1.504 V vs. RHE, and the voltage in Comparative Example 4 reaches 1.38 V vs. RHE.

[0096] From the above experimental comparison, it can be seen that the present invention greatly improves the conductivity by phosphating the FeCoNiCuMn high-entropy Prussian blue analogue, and attaching it to a nickel foam substrate further improves the conductivity of the high-entropy phosphide, increases the electrochemical surface area of ​​the catalyst, and realizes its application as an electrode material in the methanol oxidation reaction with good effect.

[0097] The FeCoNiCuMnP high entropy phosphide electrocatalyst prepared by the invention provides a new method for oxygen evolution and methanol oxidation reactions.

[0098] The FeCoNiCuMnP high entropy phosphide electrocatalyst of the present invention not only provides ideas for developing advanced methanol oxidation electrocatalysts and designing HEP electrocatalysts with high catalytic activity, but also provides a low-cost and energy-saving way to develop sustainable routes for producing value-added chemicals.

[0099] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high entropy phosphide electrocatalyst, characterized in that: The high entropy phosphide electrocatalyst comprises an active component and a conductive substrate; the active component comprises FeCoNiCuMnP high entropy phosphide nanoparticles; the FeCoNiCuMnP high entropy phosphide nanoparticles are loaded on the surface of the conductive substrate.

2. A high entropy phosphide electrocatalyst according to claim 1, characterized in that: The conductive substrate includes at least one of a titanium substrate, a nickel substrate, and a carbon cloth.

3. The method for preparing the high entropy phosphide electrocatalyst according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: obtaining solutions of cobalt salt, nickel salt, copper salt and manganese salt, and mixing them to form a blended solution A; S2: Obtaining a complexing agent solution B; the complexing agent is selected from K4Fe(CN)6 and / or K3Fe(CN)6; S3: the blended solution A in step S1 and the solution B in step S2 are mixed, and a transition metal HEPBA precursor precipitation mixture C is obtained after a coprecipitation reaction; S4: the transition metal HEPBA precursor precipitation mixture C in step S3, the solvent and the substrate are mixed, and a product I is obtained after a solvothermal reaction; S5: The product I in step S4 and the phosphoric acid compound are calcined in an inert atmosphere, and then cooled to obtain a product II, wherein the product II is a FeCoNiCuMnP high entropy phosphide electrocatalyst.

4. The method for preparing a high entropy phosphide electrocatalyst according to claim 3, characterized in that: The cobalt salt, the nickel salt, the copper salt or the manganese salt in step S1 are all selected from chlorides and / or nitrates thereof; Preferably, the molar ratio of the cobalt salt, the nickel salt, the copper salt and the manganese salt in step S1 is 1:1:1:1; Preferably, the substrate in step S4 is selected from at least one of porous titanium foam, titanium mesh, titanium sheet, porous nickel foam, and carbon cloth; Preferably, in step S3, the molar ratio of the total amount of the cobalt salt, the nickel salt, the copper salt and the manganese salt to the complexing agent is 6.5-9 mmol: 3-3.5 mmol.

5. The method for preparing a high entropy phosphide electrocatalyst according to claim 3, characterized in that: The method further includes step S3-4 between step S3 and step S4: the transition metal HEPBA precursor precipitation mixture C in step S3 is first subjected to aging, separation, water washing, alcohol washing, and drying treatment to obtain a purified solid transition metal HEPBA precursor precipitation mixture C, which is then mixed with a solvent and a substrate for a solvothermal reaction; Preferably, the phosphoric acid compound in step S5 comprises sodium hypophosphite; Preferably, the weight ratio of the sodium hypophosphite to the purified solid transition metal HEPBA precursor precipitation mixture C is 5 to 10:

1.

6. The method for preparing a high entropy phosphide electrocatalyst according to claim 3, characterized in that: The specific preparation process of the blend solution A in step S1 includes: dissolving cobalt salt, nickel salt, copper salt and manganese salt in solvent A, and performing ultrasonic dispersion after dissolution to obtain the blend solution A; the solvent A is selected from deionized water; The ratio of the solvent A to the total amount of the cobalt salt, nickel salt, copper salt and manganese salt is 150-200 mL: 6.5-9 mmol; Preferably, citric acid and / or citrate is also added to the blend solution A in step S1; The ratio of the citric acid or the citrate to the solvent A is 150-200 mL: 1-1.5 g.

7. The method for preparing a high entropy phosphide electrocatalyst according to claim 3, characterized in that: The specific preparation process of the solution B in step S2 includes: dissolving the complexing agent in the solvent B, and performing ultrasonic dispersion after the dissolution to obtain the solution B; The ratio of the solvent B to the complexing agent is 100-150 mL: 3-3.5 mmol; The solvent B is selected from deionized water; Preferably, the solvent used in the solvothermal reaction in step S4 includes deionized water; The reaction temperature of the solvent thermal reaction is 100-160°C, and the reaction time is 6-24h; Preferably, the heating rate of the calcination in step S5 is 1° C. / min to 2° C. / min, the calcination temperature is 350 to 400° C., and the holding time is 2 to 3 hours.

8. An electrocatalytic anode, characterized in that The material of the electrocatalytic anode includes the high entropy phosphide electrocatalyst according to claim 1 or 2 or the high entropy phosphide electrocatalyst prepared by the method according to any one of claims 3 to 7.

9. Use of the electrocatalytic anode according to claim 8 in the electrocatalytic oxidation of methanol to produce formate.

10. The use according to claim 9, characterized in that: The electrocatalytic anode reaches 10 mA cm in an alkaline system of 1.0 mol / L methanol during the electrocatalytic methanol oxidation reaction. -2 The required voltage for the current density is 1.31~1.45V vs.RHE, and the Tafel slope is 79~130mV dec -1 .

Citation Information

Cited By

  • High-entropy nano phosphide electrocatalyst as well as preparation method and application thereof

    CN120465035A